Acknowledgment to JCMK editorial board and peer-reviewers for contribution in 2013-2020 - Laura Dybyssova (Ķazaķstannyṇ Klinikalyķ Medicinasy, 2021)
On behalf of Journal of Clinical Medicine of Kazakhstan, we would like to express our appreciation to all editorial and advisory board members, reviewers and authors who contributed to this journal for 2013-2020 years. Beginning from 2021, the Journal of Clinical Medicine of Kazakhstan transferred to new editorial submission system (EditorialPark). The members of Editorial and Advisory board have been updated